SIMGOS EFFECTIVENESS: ASSOCIATIONS WITH HUMAN RESOURCES, MANAGEMENT SUPPORT, AND SYSTEM DESIGN AT ADINDA MEDICAL CENTRE - Nabila Yunus; Zulkarnain Sulaiman; Sunandar Said; Pratiwi Ramlan (CV. Fahr Publishing, 2026)
This study aims to analyze the relationship between human resources, management support, and system design with the effectiveness of the Generic Open Source Hospital Management Information System (SIMGOS) at Adinda Medical Centre, Sidenreng Rappang Regency, Indonesia. The study employed a quantitative analytic design with a cross-sectional approach involving 103 respondents selected using simple random sampling. Data were collected through structured questionnaires, observation, and documentation, and analyzed using univariate and bivariate analysis with the Chi-square test. The results showed that human resources had a significant relationship with the effectiveness of SIMGOS utilization (p = 0.001), indicating that users with better competence, experience, and understanding of the system tended to utilize SIMGOS more effectively. Management support also demonstrated a significant relationship with SIMGOS effectiveness (p = 0.001), reflecting the importance of organizational support, supervision, and training in ensuring optimal system implementation. However, system design did not show a significant relationship with SIMGOS effectiveness (p = 0.384), suggesting that users were still able to adapt to technical limitations within the system. The study concludes that the effectiveness of SIMGOS utilization is more strongly associated with human and organizational factors than with technological factors alone. Strengthening human resource capacity and improving management support are therefore essential strategies to enhance hospital information system utilization.